Weighting of fundamental rights in time of pandemic - Aguirre Núñez, Aroldo Ramiro (2020)
The appearance and installation in our country of the pandemic caused by the so-called covid-19, has led to the issuance of various supreme decrees, which in the name of protecting the health, the environment of the family and the community, have cut in a way Intensive certain fundamental rights of the first degree, such as freedom of transit and freedom of work. The normative argument used by the Executive Power is weak, since the preeminence of certain fundamental rights of the second degree over the other so-called fundamental rights of the first degree supposes a hypothetical scenario of imminent constitutional controversy in which the so-called weighting of fundamental rights, in which the principles of suitability, necessity and weighting or proportionalityitself will be debated, whose scenarios become very interesting and above all promising for the clarification of the conflict of rights.